Manufacturing issues with 3D-printed gears mechanical properties: A literature survey - Shaaya, Karam; Sarka, Ferenc (Design of Machines and Structures, 2024)
Additive manufacturing, often known as 3D printing, is substantially revolutionizing the industrial environment by turning new ideas into tangible items. This technology promotes innovation in various industries, like healthcare, aerospace and automotive, by allowing for the development of sophisticated, one-of-a-kind designs while reducing waste and expenses. Prompting improvements in production, additive manufacturing demonstrates a great deal of design variation while also being very efficient. This technology reforms traditional production techniques and makes solutions that were previously impossible. This research delves into the mechanical properties and production challenges of additively manufactured 3D- printed gears. The evaluation of gear performance focuses on the influence of essential characteristics, including the analysis of printing orientation and infill patterns, among other factors. Mechanical properties such as tensile and bending strength rise in a horizontal direction; conversely, in a vertical structure, the reverse is true. Concentric, grid-like infill patterns improve materials like PLA and PLA+ in strength and surface quality. This study examines significant challenges, such as thermal expansion and air gaps that affect gear reliability. Effective solutions require refining gear designs, enhancing heat dissipation, and optimizing material properties. The research findings improve comprehension of how 3D-printing parameters affect gear performance, offering valuable insights for the design and manufacture of durable, high-performance 3D-printed gears in industrial applications.